2011
DOI: 10.2169/internalmedicine.50.5320
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Genistein Protection on Pancreas Cell Damage in High Glucose Condition

Abstract: Aim An adequate β cell number is important to prevent the onset and development of type 2 diabetes. The aim of this study was to determine if phytoestrogen gesintein has protective effects against high glucoseinduced cell apoptosis in human pancreas cells, and to try to determine the possible mechanism for this protection. Methods Human pancreatic β cells were subjected to normal (5 mM) or high glucose (25 mM) with and without the presence of 100nM genistein, and also in the presence and absence of the pure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In human islets, 100 µM genistein prevented high-glucose (24 h incubation) mediated cell damage by off-setting reductions in cell growth and DNA fragmentation 109 . These effects were reversed when cells were treated with the estrogen antagonist ICI182780, suggesting that genistein’s effects were mediated by ERs 109 .…”
Section: The Anti-diabetic Actions Of Genisteinmentioning
confidence: 98%
“…In human islets, 100 µM genistein prevented high-glucose (24 h incubation) mediated cell damage by off-setting reductions in cell growth and DNA fragmentation 109 . These effects were reversed when cells were treated with the estrogen antagonist ICI182780, suggesting that genistein’s effects were mediated by ERs 109 .…”
Section: The Anti-diabetic Actions Of Genisteinmentioning
confidence: 98%
“…Genistein exerts a hypoglycemic effect in streptozocin‐diabetic rats and has been shown to improve islet β‐cell proliferation, survival, and mass via its effect on cAMP/PKA signaling and phosphorylation of extracellular signal‐related kinase (ERK)1/2 in human islets . Moreover, genistein reverses the damage to human pancreatic β cells caused by high glucose concentrations, suggesting a protective effect on these cells . Yang et al .…”
Section: Metabolic Syndrome and Genisteinmentioning
confidence: 99%
“…68,69 Moreover, genistein reverses the damage to human pancreatic b cells caused by high glucose concentrations, suggesting a protective effect on these cells. 70 Yang et al 71 demonstrated that genistein treatment significantly decreased hyperglycemia and islet cell loss in diabetic rats in a dose-dependent manner. Therefore, genistein seems to possess antidiabetic potential via its effects on islet cell preservation and improvement in glycemic control ( Figure 2).…”
Section: Effect Of Genistein On Diabetes and Risk Of Cancermentioning
confidence: 99%
“…In addition to these beneficial effects, genistein was found to protect pancreatic β cells from high glucose-induced apoptosis (72). In contrast, bafilomycin A1 reduced pancreatic islet size and impaired glucose tolerance in animal models (73,74) hypothetically linking this bacterial toxin to the development of type I diabetes (75).…”
Section: Discussionmentioning
confidence: 99%